Inhibitory activity and organic acid concentrations of metabolite combinations produced by various strains of Lactobacillus plantarum - Thu, Tran Van; Foo, Hooi Ling; Loh, Teck Chwen; Bejo, Mohd Hair (Academic Journals, 2011)
Metabolite combinations produced by Lacrtobacillus plantarum strains were studied by inhibitory activity test using Pediococcus acidilactici as indicator microorganism. The pH and cell population of L. plantarum strains were also determined. L. plantarum RG14 strain has significant (P < 0.05) lower pH but higher cell count than the other four L. plantarum strains. Inhibitory activity of metabolite combination was stronger than single strain metabolite. However, there was significantly higher (P < 0.05) inhibitory activity in Com 2 (TL1, RG11 and RI11 strains), Com 5 (TL1, RG14 and RS5 strains) and Com 7 (RG11, RG14 and RI11 strains) than other 7 metabolite combinations, which was attributed to the present of bacteriocin inhibitory compound. Lactic and acetic acids were also present in high amount in metabolite combinations. Therefore, metabolites produced by L. plantarum strains containing mainly organic acids and bacteriocin possess vast potential as feed additives for animals.